Clinical observation on effect of Chinese herbal fumigation and washing with Xiwenjing Huoxue Tongluo Decoction on limb numbness after chemotherapy for malignant tumor (中药熏洗温经活血通络方治疗恶性肿瘤化疗后肢体麻木的效果观察) - WU Ying (吴莹); TIAN Weili (田薇莉) (中西医结合护理)
Objective To investigate the effect of Chinese herbal fumigation and washing with the Xiwenjing Huoxue Tongluo Decoction on limb numbness after chemotherapy for malignant tumor. Methods Totally 120 patients with numbness of limbs after chemotherapy for malignant tumors were enrolled. The patients were divided into 2 groups with 60 cases by random number table. All patients were treated with conventional rehabilitation training, and those in the observation group were Chinese herbal fumigation and washing additionally with Xiwenjing Huoxue Tongluo Decoction, the course of treatment for both groups was 1 month. The scores of Activity of Daily Living and Simplified Mc Gill Pain Questionnaire( SF-MPQ) were observed before and after treatment. The overall curative effect was evaluated according to the improvement of the symptoms and signs. Results The ADL score of the observation group was significantly higher than that of the control group after intervention (P<0. 05). The scores of Pain Rating Index (PRI) and Present Pain Index(PPI) dimension of SF-MPQ in the observation group were lower than those of the control group after intervention (P<0. 05). The total effective rate in the observation group was higher than that in the control group (P＜0. 05). Conclusion The Chinese herbal fumigation and washing with Xiwenjing Huoxue Tongluo Decoction is effective to relieve the pain and limb numbness after chemotherapy for malignant tumor. (目的 观察中药熏洗温经活血通络方治疗恶性肿瘤化疗后肢体麻木的效果。方法 120例恶性肿瘤化疗后肢体麻木患者随机分观察组和对照组, 各60例。对照组采用常规康复训练, 观察组在对照组基础上采用中药熏洗温经活血通络方治疗。观察2组日常生活能力量表(ADL)、Mc Gill疼痛量表评分, 比较2组肢体麻木改善情况。结果 干预后, 2组ADL评分均升高, 且观察组ADL评分高于对照组, 差异有统计学意义(P＜0. 50)。干预后, 2组Mc Gill疼痛量表各维度评分均降低, 且观察组PRI、PPI维度评分低于对照组, 差异有统计学意义(P＜0. 05)。观察组总有效率高于对照组, 差异有统计学意义(P＜0. 05)。结论 采用中药熏洗温经活血通络方治疗, 有助于缓解恶性肿瘤化疗后肢体麻木患者的疼痛, 改善肢体麻木, 提高生活质量。)